A Schottky Rectifier Design Using EM Simulation Tools for RF Energy Harvesting Applications - Partal, Hakan P.; Belen, Mehmet Ali; Zorlu-Partal, Sibel; Ince, Ahmed Tahir (IEEE, 2015)
In this paper, a zero-bias Schottky Rectifier design for ISM band energy harvesting applications is presented. Microwave circuit and EM simulations along with fabricated circuit results are demonstrated. To achieve a successful harvester module, the rectifier circuit with a high sensitivity Schottky diode is designed and impedance matched for the best conversion efficiency. Then the rectifier RF input power vs. the harvested DC output voltage measurements are tabulated. The simulated and measured results are compared and a good agreement has been achieved for this nonlinear circuit model.
Keywords: EM simulations; RF energy harvesting; RFID; Schottky rectifier; Engineering